Carnavalização no espaço discursivo da música: do renascimento ao romantismo - Alexandre Fernandes Guimaraes (2011)
The present work investigates the carnivalization phenomenon in the western music produced between Renaissance and Romanticism musical periods. The musical text is here treated according to Mikhail Bakhtin theories about the discourse, based on the hypothesis that the carnivalization is applied to the musical discourse; therefore, it is a worthy theory to a more profound study in the musicological field. The methodological-theoretical support of the analysis, adapted from Bakhtin studies about Dostoyevsky Romanesque genres, consists in the pursuit of musical constructions that adequate to the three peculiarities of the carnivalesque genre and also in the inclusion of the examples in one or more among the four carnivalesque cosmovision categories. I present a general view about dialogism and polyphony, fundamental concepts for the comprehension of the general aspects of Bakhtins thoughts, which also possess interfaces with the musicological analytical models. In order to achieve the main objective of this work, I chose as corpora representative works from the analyzed periods, which incorporate the musical carnivalization phenomenon between the period that have witnessed tonalisms birth to the period which precedes the languages that abolished tonalism. Throughout this work, I demonstrate that the musical discourse can also strongly express itself as dialogic-polyphonic, allowing in the text the presence of carnivalesque cosmovision elements, and producing the phenomenon that I here name musical carnivalization.